Scaling the value creation capacity of non-profit organisations through an evolving partnering portfolio : learning from a case in practice - Daniels, Desiree Margaret (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.